Anti-collision performance of RC columns strengthened with a composite of FRP grid and UHPC. (September 2022) - Liu, Xin; Zheng, Yu-Zhou; Fang, Qin; Zhou, Chang; Yang, Ya; Xiang, Heng-Bo; Yan, Hai-Chun
Abstract: To improve the anti-collision performance of existing reinforced concrete (RC) columns subjected to vehicle impact loading, this paper proposes a composite strengthening method involving the use of fiber-reinforced plastic (FRP) grid and reinforced ultra-high performance concrete (UHPC). An RC column strengthened with the composite of FRP grid and UHPC and an ordinary RC column were prepared to investigate their anti-collision performance under impact loading. Using the methods of numerical analysis and tests, the effects of the vehicle impact velocity, reinforcement layer thickness, and material strength on the anti-collision performance were discussed. The test results showed that the lateral displacement of the RC column significantly decreased after strengthening with the composite. This indicated that the anti-collision performance of RC columns strengthened with the composite of FRP grid and UHPC can be effectively improved. The numerical results showed that the lateral displacement of the strengthened columns was increased by 37.8 % with an increase in the impact velocity from 3.69 m/s to 4.3 m/s; however, the impact velocity had no evident effect on the impact force acting on the surface of the RC columns. In addition, the anti-collision properties of the strengthened RC columns were significantly enhanced with the increase in the FRP grid–UHPC composite thickness and material strength. The lateral displacement of the strengthened RC columns reduced by 7.5 %–13.5 %, and its peak impact force increased by 14.9 %–33.2 % with an increase in the composite thickness from 20 mm to 40 mm. Moreover, the lateral displacement of the strengthened RC columns reduced by 14.5 %–36.1 %, and its peak impact force increased by 10.9 %–46.4 % with the increase in the compressive strength of concrete from 45 MPa to 210 MPa.